LIVING AL-QUR’AN DI MEDIA SOSIAL: STUDI ETNOGRAFI VIRTUAL PADA AKUN TIKTOK @MY INSPIRATION - Abdan Syakuro; Ahmad Gungun Fariq; Ainun Nafisa; Choirul Azam Firdaus; Ecep Ismail; Asep Abdul Muhyi (Adisam Publisher, 2025)
This research explores the reception of the Qur'an in the digital era through a TikTok platform called My Inspiration using a descriptive qualitative method. The analysis focuses on several videos or content related to three recommended practices for having children, the meaning of Surah At-Talaq verses 2–3 commonly referred to as the